Thrombosed pulmonary artery aneurysm. Presenting two cases - Carlos Ramos Emperador; Gerardo Senra Piedra; Mariam González Gorrín; Michel Ley Rodríguez (ECIMED, 2011)
The pulmonary artery aneurysm is an anomalous dilation of the trunk of this artery or one ofits main branches. The presence of pulmonary hypertension and processes that affect thevascular wall are the phisiopathological premises for their development. It is not a very frequentillness, of multiple aetiology, that can established without symptoms, with unspecificsymptoms or just start with complications; as rupture of the aneurysm, compression of nearstructures or thrombus formation. Their natural history is not known and it is thought that itsrelated to the causes that give them origin. In this paper we present two patients with pulmonaryartery aneurysm, secondary to severe pulmonary hypertension in the course of aninterauricular communication, complicated with thrombus adhered to the walls of the pulmonaryartery. The diagnosis was carried out by transthoracic and transaesophagic echocardiography.